Physicochemical changes in enamel submitted to pH cycling and bleaching treatment - Eskelsen E; Catelan A; Hernades NMA; Soares LES; Cavalcanti AN; Aguiar FHB; Suzy Liporoni PC (Dove Medical Press, 2018)
Evania Eskelsen,1 Anderson Catelan,1 Natália Maria Aparecida Pinto Hernades,2 Luís Eduardo Silva Soares,3 Andrea Nóbrega Cavalcanti,4 Flávio Henrique Baggio Aguiar,2 Priscila Christiane Suzy Liporoni1 1Department of Dentistry, University of Taubaté, Taubaté, São Paulo, Brazil; 2Department of Restorative Dentistry, Piracicaba Dental School, University of Campinas, Piracicaba, São Paulo, Brazil; 3Laboratory of Biomedical Vibrational Spectroscopy, Research and Development Institute, University of Vale do Paraíba, São José dos Campos, São Paulo, Brazil; 4Department of Restorative Dentistry, School of Medicine and Public Health of Bahia and Federal University of Bahia, Salvador, Bahia, Brazil Objective: The purpose of this study was to assess the hardness, mineral content, surface roughness, and micromorphology of sound and slightly demineralized enamels, before and after bleaching procedure using 10% carbamide peroxide.Methods: Sixty bovine dental blocks were randomly divided into the following two groups: 30 slabs were submitted to three cycles of pH and 30 slabs were noncycled. Hardness (n=10) was measured using the microhardness tester with Knoop indenter under a 50 g load for 5 seconds. The calcium/phosphate (Ca/P) ratio (n=10) was obtained using a micro-energy-dispersive X-ray fluorescence (μ-EDXRF) spectrometer. The measurement of roughness average (n=10) was performed using a surface roughness tester. Specimens were bleached 6 hours/day during 21 days, and then, physicochemical properties were re-evaluated. Two additional specimens were carried out to evaluate surface micromorphology using the scanning electron microscopy. Data were statistically analyzed by ANOVA and Tukey’s test (α=0.05).Results: Sound and slightly demineralized enamels showed no difference in Ca/P ratio after dental bleaching according to the µ-EDXRF analysis, but the Ca/P ratio decreased after bleaching for slightly demineralized enamel. Bleaching treatment decreased the hardness and increased the surface roughness, causing micromorphology alterations.Conclusion: Therefore, bleaching procedure promoted change in bovine enamel surface and increased the demineralization of slightly demineralized enamel but not affected the mineral content of sound enamel. Keywords: tooth bleaching, dental enamel, chemical properties, pH cycling, microhardness, roughness